Effectiveness of Emotion-Focused Therapy on Assertiveness and Anger Rumination in Women Victims of Domestic Violence - Leshani , Sara; Anasseri, Mehryar; Ghahremani, Maryam (Psychology of Woman Journal, 2023)
Objective: Domestic violence, or violence against women within the family, is the most common form of violence. The current study aimed to determine the effectiveness of emotion-focused therapy on assertiveness and anger rumination in women victims of domestic violence. Methods and Materials: This study was a quasi-experimental research with a pre-test - post-test design. The population consisted of all women victims of domestic violence in Isfahan city in the year 2023. In this study, 26 women victims of domestic violence were selected using a purposive non-random method and then randomly assigned into an experimental group (13 persons) and a control group (13 persons). The experimental group participated in 9 sessions of emotion-focused therapy and eventually, after attrition, 12 participants successfully completed the treatment. The control group did not receive any intervention. It is worth noting that to equate the number of participants in both the experimental and control groups, members were randomly removed from the control group equivalent to the attrition in the experimental group. In this research, the Gambrill and Richey (1975) Assertiveness Questionnaire and the Spielberger et al. (2001) Anger Rumination Scale were used. The collected data were analyzed using multivariate and univariate covariance analysis statistical models and SPSS.22 software. Findings: The results showed that emotion-focused therapy significantly improved assertiveness (F=26.28, P<0.001) and anger rumination (F=44.93, P<0.001). Conclusion: Based on the findings of the current study, interventions based on this approach can effectively improve assertiveness and anger rumination in women victims of domestic violence.